PELATIHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA SISWI SMA BINA LESTARI KECAMATAN GANDUS SEBAGAI UPAYA PENCEGAHAN KANKER PAYUDARA - Ismar Agustin; Intan Kumalasari; Herawati Jaya (LPPM Univ. Ibn Khaldun Bogor, 2021)
Breast cancer has become one of the most common female malignant tumors in the world and a leading cause of death. Disease is prevalent in low- and middle-income countries where most cases are diagnosed at an advanced stage. Still finding cases at an early stage makes early detection and screening efforts very important. The prognosis for long-term cure is relatively high if cancer is detected early and managed regularly. Health education is a practical and effective method to raise awareness of women about the importance of early detection of breast cancer. Health education has been proven to be effective in increasing knowledge and frequency of breast examinations with BSE. This activity aims to provide training through increasing the knowledge and skills of young women, especially Bina Lestari Palembang high school students in early detection of breast cancer with BSE. The training method is counseling by providing education and breast self-examination with BSE. Pre test and post test before and after training. The results of the counseling had a positive impact on the training participants where most of the students experienced a significant increase in knowledge after attending breast self-examination training as an effort to prevent breast cancer.